Phytochemical profiling of little millet (Panicum sumatrense Roth.) - Ritu Sharma; Devendra Kumar
The little millet (Panicum sumatrense Roth.) has great potential to develop as functional food and source of nutraceuticals to prevent metabolic disorders. The aim of the current study aim is to identify the bioactive compounds present in little millet (Panicum sumatrense). The bioactives were analysed using GC-MS and UHPLC-QTOF-MS. GC-MS analysis majorly showed the presence of hydrocarbons, fatty acids, and terpenes, while UHPLC-QTOF-MS analysis showed 22 secondary metabolites, including quercetin, palmitic acid,gb(B-stigmasterol,luteolin, and kaempferol. ICP-MS detected 21 macro- and micro-elements, with potassium (K), magnesium (Mg), and molybdenum (Mo) as the major elements. FAME analysis revealed the presence of linoleic acid (42%), oleic acid (34.1%), and palmitic acid (15.7%)as the major fatty acids. Amino acid profiling indicated the presence of essential, non-essential, and non-proteinogenic amino acids. These findings suggest that P. Sumatrense could be a valuable natural source of bioactive metabolites and can be utilised to develop value-added functional foods.s